The broker - Grisham, John (Buena Park, Calif. : Morning Glory Press, 1999)
Racially mixed seventeen-year-old Lauren, the daughter of drug users, is pressured to have sex with her boyfriend and questions her promise to herself to stay a virgin until she is married.
Keywords: Sexual abstinence